Comparative of paraffin and turpentine used in wax resist dying on batik fabric / การเปรียบเทียบการใช้พาราฟินและยางสนในการลงลายผ้าบาติก - มะแซ, มาหามะสูไฮมี; สีคง, เล็ก; คุปตานนท์, กัลยาณี; คงสง, พีรวัส; เพิ่มพูน, พัชรี; พิศสุวรรณ, พิชญา; สนิ, ซูไฮดี; ศิริคุณ, วิทยา; โรจนานุกูล, จุฬาลักษณ์ (Journal of Community Development Research (Humanities and Social Sciences), 2014)
วัตถุประสงค์ของการศึกษาในครั้งนี้ เพื่อพัฒนาการเปียกและการซึมผ่านของเทียนไขในการลงลายผ้าบาติก เพื่อให้ประสิทธิภาพในการผลิตผ้าบาติกที่มีคุณภาพดีและง่ายต่อการลงเทียนปิดส่วนที่ไม่ต้องการให้ติดสี เทียนไขที่ใช้ในการศึกษาในครั้งนี้ ได้ใช้พาราฟินและยางสนเรซินผสมกัน มาหลอมในเตาอบที่อุณหภูมิ 100°C นาผ้าฝ้ายมาขึงให้มีความเรียบ บนกระจกสไลด์ขนาด 5 x 5 เซนติเมตร หลังจากนั้น จึงนาไปหยดด้วยเทียนไขแล้วปล่อยให้แห้งที่อุณหภูมิห้อง ก่อนนา ผ้าฝ้ายไปหยดเทียนนั้น ได้นาผ้าไปทาความสะอาดด้วยการแช่ในสารละลายโซเดียมไฮดรอกไซด์ความเข้มข้น 1 โมลาร์ แช่ไว้เป็นเวลา 24 ชั่วโมง แล้วทาการล้างให้สะอาดผึ่งลมให้แห้ง การวิเคราะห์สมบัติทางความร้อนได้ใช้เครื่องวัดการเปลี่ยนแปลงความร้อนของวัสดุ (Differential scanning calorimetry, DSC) มีการวัดความหนืดด้วยเครื่องวัดความหนืด ศึกษาลักษณะการหยดของเทียนไขบนผืนผ้าด้วยการถ่ายภาพจากเครื่องวัดมุมสัมผัสและหาค่ามุมสัมผัส โดยการฉีดเทียนไขหลอมออกจากหัวฉีดระยะห่าง 1 มิลลิเมตร ปริมาตรเทียนไขหลอม 14 ไมโครลิตร อีกทั้งยังวัดความหนาของเทียนไขที่ติดบนผืนผ้า ด้วยไมโครมิเตอร์ หลังจากนั้น ได้นาผ้าที่ทาการเขียนด้วยเทียนไขมาย้อมสีและทาการเคลือบด้วยโซเดียมซิลิเกตที่ใช้ในการเคลือบผ้าบาติกแล้วทาการต้มด้วยน้าเดือดเพื่อล้างเทียนออก ทาการเปรียบเทียบลักษณะของเส้นเทียน จากผลการศึกษาการใช้พาราฟินผสมยางสน มีค่ามุมสัมผัสต่ากว่า (21°) พาราฟิน (39°) และยางสน (121°) วัดมุมสัมผัสจะมีค่าที่สัมพันธ์กับค่าความหนืด การใช้พาราฟินผสมกับยางสนสามารถพัฒนาการใช้ลงลายของผ้าบาติก เพราะมีค่ามุมสัมผัสที่เหมาะสมมีการแผ่กระจายบนผืนผ้าได้เป็นอย่างดีและปิดส่วนที่ไม่ต้องการให้ติดสีได้ดีอีกด้วย ซึ่งเมื่อเปรียบเทียบกับการใช้พาราฟินและยางสนเพียงอย่างเดียวนั้นจะให้ค่ามุมสัมผัสที่สูงและให้ความหนาของเทียนมากกว่า คำสำคัญ: ผ้าฝ้าย พาราฟิน ยางสน เทียนไข ผ้าบาติก The objective of this study is to improve wet ability of the molten candle waxes on surface of fabrics that could be more easily used in wax resist dying to produce high quality batik products. Candle waxes were prepared by mixing with paraffin and turpentine resin. The sample batches were melted in oven at 100ºC. Cotton fabric (5×5 cm.) was stretched on glass slide, immediately drop the melted wax and left to dry at room temperature. The fabrics before wax droplet were immersed in 1 M NaOH solution 24 h, rinsed normally and were then dried. Thermal property was analyzed by differential scanning calorimetry (DSC). Viscosity of the molten candle waxes was observed by using viscometer. The formation of the wax droplet in terms of contact angles were investigated at room temperature using a contact angle meter (OCA15EC) with a gap distance between eject head and cotton fabric surface of 1 mm, and the waxes volume of 14 μL. The wax droplet thickness was measured by micrometer. Cotton fabrics were immersed in batik textile dye solution and coated with batik sodium silicate, wax resist dying on batik fabric after boil were investigated and compared. It was found from the experimental study that the paraffin and turpentine mixed batch exhibited lower contact angle (21°) than that of pure paraffin (39°) and pure turpentine (121°). It should be noted that contact angle correlates to the viscosity of the molten sample. The paraffin mixed with turpentine molten sample can improve the contact angle of cotton fabric surface. It was excellent and spread on cotton fabric surface. The paraffin mixed with turpentine droplet on cotton fabrics can improve the wet ability of fabrics surface, leading to the enhancement of resist dying on batik fabric. The utilization of pure paraffin and pure turpentine samples has influence only the increasing droplet contact angle and thickness. Keywords: Cotton fabric, Paraffin, Turpentine, Candle waxes, Batik fabric
Keywords: ผ้าฝ้าย พาราฟิน ยางสน เทียนไข ผ้าบาติก Cotton fabric, Paraffin, Turpentine, Candle waxes, Batik fabric